Efficiency of the Implementation of Centrifugal Extractor for the Reduction of Dust Concentration in the Planing of a Lumber Mill - Paz Corrales, Olivia Anyelina; Gonzales Medina, Luz Eleana; Zuñiga Esquivel, Marcos Yeremy; Salas Guillen, Maria fernanda; Zvietcovich Cornejo, Gloria Natalie; Díaz Salas, Carmen Cecilia (LACCEI, 2025)
This study was conducted at a sawmill to evaluate the effectiveness of a centrifugal fan in reducing respirable and inhalable dust concentrations during the wood planing process. Pre-intervention sampling was performed, where dust levels were measured for three days in five workers, using standardized NIOSH methods (0500 and 0600). Initial results showed weighted concentrations of respirable and inhalable dust that exceeded the established permissible limits, where respirable dust concentrations of 4,599, 5,109, 4,525, 4,681 and 5,595 mg/m3, exceeded the permissible limit value (PLV) of 3 mg/m3 according to D.S. 015-2005-SA. For inhalable dust, concentrations were 12,762, 10,875, 11,759, 13,217 and 11,316 mg/m3, also exceeding the VLP of 10 mg/m3. After the installation of the centrifugal extractor, a significant reduction in dust concentration was observed. Once the extractor was installed, post-monitoring of respirable dust concentration was carried out, obtaining values ​​of 1,276; 1,390; 1,399; 1,215 and 1,238 mg/m3. On the other hand, the inhalable dust values ​​are 1,971; 1,701; 1,922; 2,136 and 2,098 mg/m3, which are below the VLP. The extraction system efficiency reached 74.99% for respirable dust and 83.84% for inhalable dust. The data obtained show that, after the intervention, dust concentrations were within acceptable levels, in line with occupational health regulations and highlighting the importance of implementing control measures in the work environment to protect workers' health.